Best Jewish books for children and teens - Silver, Linda R. (Philadelphia, PA : The Jewish Publication Society, 2010)
Linda Silver selected the titles that "represent the best in writing, illustration, reader appeal, and authentically Jewish content--in picture books, fiction and non-fiction, for readers ranging from early childhood through the high school years."--Page 4 of cover.
Recomended reading by subject. Jewish rites and customs ; Holidays ; The Bible ; Folklore ; History ; Immigrant life ; The Holocaust and World War II ; Israel and Zionism ; Contemporary issues ; Famous Jews ; Judaism and other religions -- Notes -- National Jewish book award winners -- Sydney Taylor book award winners -- Titles by recommended reading levels.
Includes bibliographical references (pages 271-272) and indexes by title, author, illustrator, and subject.
Print version record.
Keywords: Best books; Judaism -- Bibliography; Jewish literature -- Bibliography; Jewish teenagers -- Books and reading -- Bibliography; Jewish children -- Books and reading -- Bibliography; REFERENCE -- Bibliographies & Indexes; Electronic books